Consumer social responsibility: is it a new barrier for international marketers?. (2015) - Ma, Jieqiong; Yang, Jie; Kalliny, Morris; Roy, Douglas
The importance of corporate social responsibility in the business world has gained interest among scholars within the last two decades. However, despite considerable work on corporates' social responsibility towards the community and environment, the social responsibility of consumers remains largely unexplored. As consumers become more aware of the social consequences of their purchases, is it possible that consumer social responsibility will become a new barrier for international marketers? The purpose of this study is to investigate the relationship between consumer social responsibility, consumer ethnocentrism, and consumer demographic variables that may influence this relationship. After sampling 206 US consumers, our results indicate that consumers with high social responsibility tend to have negative attitudes towards foreign products. In addition, we find that demographic segmentations such as age, gender, income, and ethnicity further alter such negative attitudes. In contrast, we find that consumers' education level has little impact on negative attitudes towards foreign products.